“Signifying Monkey” –The Guardian of African Tradition (European Journal of Language and Literature, 2018)
African oral tradition is much more than just a story. It is the history of one nation. It is a code of laws under which people live and die. However, the oral tradition is also a rich area of wordplays and high philosophy, which represent the foundation of today's African and African-American literature. Proverbs, ritual songs, epics, all of this is the foundation of an advanced society. In reality, the keepers of the culture are griots - storytellers. In fiction, these are trickster gods in the shape of sacred animals. Only one of them is a cunning monkey, thanks to which a whole genre of double-thinking has emerged. The monkey is a shadow in the proverbs and inspiration for storytellers. The double-thinker and the representative of reason and justice through stunning wordplays. Two-voiced messages which are a feature of the highly advanced philosophical nation that possessed cultural richness even in the era of oral tradition. The tradition that still exists.